ANALYSIS OF THE APPLICATION OF TEACHING METHODS IN TEACHING MANDARIN VOCABULARY AT UNIVERSITY LEVEL - Nirdayanti Mustarih; Asmuliyati Nahnu; Nur Nasharuddin Noni; Sri Khaerani Rahman (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study explores the challenges and teaching methods designed to enhance Chinese vocabulary acquisition at the university level. Vocabulary acquisition is crucial for mastering a language, and in the case of Chinese, its complexity presents unique challenges for both learners and educators. The research employed a qualitative narrative design, conducting interviews with 10 Chinese language lecturers from various universities to gather insights into the methods and obstacles in vocabulary teaching. Data was collected using three primary methods: observations, questionnaires, and a comprehensive literature review. The findings of this study reveal a diverse range of approaches teachers employ. Approximately 60% of teachers adapt their methods based on student needs, indicating that flexibility and adaptability are key components of their teaching strategies. In contrast, 40% of teachers maintain a consistent teaching approach, believing that a structured framework helps students better understand the material and retain vocabulary. Despite these varied strategies, memory retention remains a significant challenge, with 50% of teachers reporting that their students struggle to retain Chinese vocabulary effectively. This highlights students' difficulty mastering a language with such a complex writing system. The study proposes a balanced approach, integrating flexible and consistent teaching methods, which are essential for overcoming the inherent challenges in Chinese vocabulary acquisition. Additionally, multimedia tools and digital technologies have effectively engaged students and enhanced vocabulary retention. The research concludes that refining current teaching methods—including structured routines, task-based learning, and spaced repetition—is necessary for improving student engagement and memory retention in Chinese language education.